Bi-species imposex monitoring in Galicia (NW Spain) shows contrasting achievement of the OSPAR Ecological Quality Objective for TBT. Issue 2 (30th January 2017) - Ruiz, J.M.; Carro, B.; Albaina, N.; Couceiro, L.; Míguez, A.; Quintela, M.; Barreiro, R.
Abstract: Imposex is decreasing worldwide after the total ban on tributyltin (TBT) from antifouling paints. In order to assess improvement in the NE Atlantic, the OSPAR Convention designed an Ecological Quality Objective (EcoQO) based on the VDSI (vas deferens sequence index, an agreed measure of imposex) in the rock snail Nucella lapillus ; wherever this is not available, the mud snail Nassarius reticulatus was proposed as a proxy. We determined VDSI in Galician populations of rock ( n ≥ 34) and mud ( n ≥ 18) snails at regular intervals from pre-ban times until 2009 and 2011, respectively. While imposex in the former started decreasing in 2006 and by 2009 the EcoQO had been met in the area, VDSI in the latter was not significantly reduced until 2011 and values contradict such an achievement. This suggests that the OSPAR imposex bi-species scheme may not be of direct application in the current post-ban scenario. Highlights: Imposex resulting from TBT pollution was regionally monitored over > 10 years. In Nucella lapillus, it significantly declined soon after the 2003 European total ban. In the mud snail Nassarius reticulatus, it had not fallen to a similar extent by 2011. Altogether, the results confuse the achievement of target water quality in the area. The bi-species imposex scheme set by OSPAR may not apply in post-ban scenarios.